2018
DOI: 10.1177/0021998318808024
|View full text |Cite
|
Sign up to set email alerts
|

Posidonia oceanica leaves for processing of PMDI composite boards

Abstract: Posidonia oceanica leaves (seagrass) are collected almost in all the Mediterranean seashores as spoils and disturbing material with additional cost for removal from the coastline. Seagrass, however, is known for its interesting properties, such as decay, fire and moisture resistance as well as insulation. Research for using this material in composing boards was initiated. This study looks into the possibility of using these waste marine plants for the production of alternative building material in the form of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…They found that increasing the amount of tapioca starch flour in the seaweed adhesive resulted in improved mechanical properties. Kuqo et al [17] made particleboards from Possidonia oceanica leaves and used isocyanate resin as a binder. They reported that seagrass leaves are propitious for application in construction and furniture industries.…”
Section: Introductionmentioning
confidence: 99%
“…They found that increasing the amount of tapioca starch flour in the seaweed adhesive resulted in improved mechanical properties. Kuqo et al [17] made particleboards from Possidonia oceanica leaves and used isocyanate resin as a binder. They reported that seagrass leaves are propitious for application in construction and furniture industries.…”
Section: Introductionmentioning
confidence: 99%
“…The thermal conductivity (λ) and the volume of PO fibers (POF) have an exponential correlation, according to regression results in figure 11 and equation (14):…”
Section: Thermal Conductivitymentioning
confidence: 98%
“…Experimental research has been conducted by Kuqo et al [14] to examine the impact of PO fibers in the process of creating lightweight concrete. They discovered that fibers had a number of intriguing qualities, including resistance to heat, fire, and moisture, and that they may be used as an inexpensive raw material to create composites.…”
Section: Introductionmentioning
confidence: 99%
“…Much work has focused on the use of seagrass leaves bonded with organic binders (pMDI, UF, etc.) to produce medium-density fiber/particleboards [ 17 , 18 ]. In other cases, researchers have used mineral binders such as cement for the production of insulation composites [ 19 ].…”
Section: Introductionmentioning
confidence: 99%